A [2,3]-Wittig rearrangement approach towards the stereoselective synthesis of the C(10)–C(20) backbone of the fumonisins - Vleggaar, Robert (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.